Black Women Educators’ Activism: The Evolution of a Black Feminist Pedagogy - Pierre, Yvette (European Scientific Journal, ESJ, 2023)
Exploring the historical narrative of activism among black American women offers valuable insights into their significant role in advocating for equal and high-quality educational opportunities within their community. It unveils their cultural and political acumen, attitudes, and dedication, which they extend into the realm of teaching. Their moral philosophies and sense of purpose have been instrumental in the creation of a black feminist pedagogy that has evolved within the frame of black women’s resistance to oppression and the ensuing battle for collective survival and institutional change (Collins, 1990).